2006
DOI: 10.1007/s00296-006-0164-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with anakinra in the hyperimmunoglobulinemia D/periodic fever syndrome

Abstract: Hyperimmunoglobulinemia D/periodic fever syndrome is caused by recessively inherited mutations in the mevalonate kinase gene and is characterized by persistently high polyclonal serum IgD titre and recurrent febrile attacks. No conventional therapy exists for preventing the typical recurrent inflammatory picture of patients. A host of studies have evidenced that elevated levels of various cytokines, such as interleukin-1 (IL-1), mark febrile attacks in this disease and that IL-1 might represent a suitable ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 10 publications
0
36
0
2
Order By: Relevance
“…Infliximab, a humanized monoclonal antibody against TNF-α, and tocilizumab, a humanized monoclonal antibody against the IL-6 receptor, might also be thinkable alternatives. So far, some children have been successfully treated with etanercept and with different anti-IL-1 drugs (Bodar et al, 2011;Caorsi et al, 2012;Galeotti et al, 2012;Hoffman, 2009;Rigante et al, 2006). If either of these treatments are not effective a switch to the other can be considered, because some patients have a good response to anti-IL1 drugs but not to etanercept, and vice versa (Caorsi et al, 2012;van der Hilst and Frenkel, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infliximab, a humanized monoclonal antibody against TNF-α, and tocilizumab, a humanized monoclonal antibody against the IL-6 receptor, might also be thinkable alternatives. So far, some children have been successfully treated with etanercept and with different anti-IL-1 drugs (Bodar et al, 2011;Caorsi et al, 2012;Galeotti et al, 2012;Hoffman, 2009;Rigante et al, 2006). If either of these treatments are not effective a switch to the other can be considered, because some patients have a good response to anti-IL1 drugs but not to etanercept, and vice versa (Caorsi et al, 2012;van der Hilst and Frenkel, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no evidence-based treatment available for HIDS (Korppi et al, 2011). Thus far, some children have been successfully treated with etanercept and others with IL-1 antagonists (Bodar et al, 2011;Caorsi et al, 2012;Galeotti et al, 2012;Hoffman, 2009;Rigante et al, 2006).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…[1,11,[14][15][16] Colchicine and prednisolone had no beneficial effect in preventing the recurrence of attacks in our patient. Recent studies with the HMG-CoA-reductase inhibitor simvastatin have brought hopeful results for the treatment of this disease [3,4,17,18] Simon et al [4] reported that six patients with HIDS and proven MVK deficiency were followed up for two treatment periods with simvastatin, 80 mg/day, or placebo for 24 weeks separated by a four-week washout period in a double-blind manner Important reductions in the number of attacks and decreased urinary mevalonate were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Anakinra (1 g/kg/day) was first shown to reduce the overall number and severity of febrile attacks in a 7-year-old girl with MKD in 2006 (35). Two sisters with MKD also exhibited normal levels of inflammatory markers and a substantially improved quality of life after starting anakinra (36).…”
Section: Mkd Treatment Optionsmentioning
confidence: 99%